2014
DOI: 10.5194/tc-8-997-2014
|View full text |Cite
|
Sign up to set email alerts
|

SMOS-derived thin sea ice thickness: algorithm baseline, product specifications and initial verification

Abstract: Abstract. Following the launch of ESA's Soil Moisture andOcean Salinity (SMOS) mission, it has been shown that brightness temperatures at a low microwave frequency of 1.4 GHz (L-band) are sensitive to sea ice properties. In the first demonstration study, sea ice thickness up to 50 cm has been derived using a semi-empirical algorithm with constant tie-points. Here, we introduce a novel iterative retrieval algorithm that is based on a thermodynamic sea ice model and a three-layer radiative transfer model, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
239
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(265 citation statements)
references
References 62 publications
(99 reference statements)
6
239
0
1
Order By: Relevance
“…Since the launch of ESA's Soil Moisture and Ocean Salinity (SMOS) mission in 2009, it has been demonstrated that passive microwave measurements at L-band are well suited for sea ice thickness retrieval [2][3][4][5]. Having a large sensitivity to thin sea ice of 0.5 to 1 m, L-band measurements nicely complement Cryosat-2 altimeter data, which show increasingly large relative uncertainties for thin ice below 1 m [6].…”
Section: Introductionmentioning
confidence: 74%
“…Since the launch of ESA's Soil Moisture and Ocean Salinity (SMOS) mission in 2009, it has been demonstrated that passive microwave measurements at L-band are well suited for sea ice thickness retrieval [2][3][4][5]. Having a large sensitivity to thin sea ice of 0.5 to 1 m, L-band measurements nicely complement Cryosat-2 altimeter data, which show increasingly large relative uncertainties for thin ice below 1 m [6].…”
Section: Introductionmentioning
confidence: 74%
“…Still, large uncertainties remain in the accuracy of the resulting SIT estimates (larger than 0.5 m) due to uncertainties in the snow depth and the sea ice density (Zygmuntowska et al, 2014). A new database based on CryoSat-2 has been provided (Laxon, 2013;Ricker et al, 2014) and has been made available in near-real time (Tilling et al, 2016). Finally, methods for SIT retrieval based on measurements of the brightness temperature at a low microwave frequency of 1.4 GHz (L-band: wavelength λ a = 21 cm) have been developed in preparation for the European Space Agency's (ESA) Soil Moisture and Ocean Salinity (SMOS) mission (Heygster et al, 2009;Kaleschke et al, 2010Kaleschke et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…But results of the study can enlighten several aspects of the snow on ice problem which is important today. The difference between MY and FY regarding snow cover, estimation of energy fluxes from ocean to atmosphere in coupled models, the impact on snow cover on satellite altimeter retrievals of ice thickness and 20 passive microwave retrievals of thin ice thickness (Tian-Kunze et al;.…”
Section: Resultsmentioning
confidence: 99%